Evalvacija zaupanja vrednih digitalnih arhivov pri projektu reUSE! - Kavčič-Čolić, Alenka (Knjižnica, 2007)
Under the European eContent project reUSE! five partner institutions have aimed to establish trusted digital archives in order to fill them with digital copies and master files that have been the basis for printed publications publisher by the public sector institutions. The main goals of the project have been to increase public access to these publications and to achieve their long-term preservation. The role of the National Library of Germany, the Faculty for Civil and Geodetic Engineering of the University of Ljubljana, and the National and University Library of Slovenia was to critically evaluate and guide the development of the partners' digital archives. In this regard, a specific evaluation methodology, which focused on the organizational, technical and user aspects of the digital archives, was set up. The methodological approach with special emphasis on the organizational and user aspects is presented in the article.
Keywords: digitalni arhivi; digitalni repozitoriji; evalvacija; zaščita; metodologija; mednarodni projekti